2016
DOI: 10.1002/hyp.10794
|View full text |Cite
|
Sign up to set email alerts
|

Goat trampling affects plant establishment, runoff and sediment yields over crusted dunes

Abstract: Abstract:Mainly attributed to goat and sheep trampling, the sand dunes at the Israeli and the Egyptian sides of the border present contrasting geomorphological conditions. In an attempt to assess the trampling effect upon vegetation, runoff and sediment yield, two pairs of plots and miniplots (each pair contains a trampled plot and a control) were constructed during 1991 and monitored during 1991-1995. In order to assess the impact on vegetation, three pairs of vegetation plots, subjected to light, medium and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 58 publications
0
7
0
1
Order By: Relevance
“…A rise in dryland surface albedo could create a large impact on the mean global albedo, where slight alterations greatly affect global climate patterns 41 , and this could be of growing concern with the degradation and disturbance of dryland biocrusts observed globally 6 9 10 42 43 44 45 46 . To explore the global effects of rising dryland surface albedo, we utilized the MODIS/Köppen ecosystem classification scheme from Elbert et al .…”
Section: Resultsmentioning
confidence: 99%
“…A rise in dryland surface albedo could create a large impact on the mean global albedo, where slight alterations greatly affect global climate patterns 41 , and this could be of growing concern with the degradation and disturbance of dryland biocrusts observed globally 6 9 10 42 43 44 45 46 . To explore the global effects of rising dryland surface albedo, we utilized the MODIS/Köppen ecosystem classification scheme from Elbert et al .…”
Section: Resultsmentioning
confidence: 99%
“…Trampling tends to cause a disruption of hydrological barrier caused by biocrusts, which could explain the positive effect of disturbance in this study. Previous studies have also reported that trampling increased infiltration (Belnap & Eldridge, 2003;Bowker et al, 2013;Chung et al, 2019;Faist et al, 2017;Kidron, 2016;Zaady et al, 2013) (Table 5). On the contrary, some authors found that trampling resulted in decreased infiltration (Barger et al, 2006;Chamizo, Cant on, Lázaro, et al, 2012;Herrick et al, 2010).…”
Section: Influence Of Biocrust Disturbance On Infiltrationmentioning
confidence: 60%
“…Goats trampling over crusted dunes caused reduction in runoff and sediment yield (Kidron, 2016). Elliott and Carlson (2004) investigated seasonal effects on infiltration capacity of a hill-country farm (sheep grazing) in Waikato (New Zealand).…”
Section: Tramplingmentioning
confidence: 99%
“…The hydrological implications of grazing by SRs were increased runoff and decreased evapotranspiration rates (Wood et al., 2008). High attention has been paid to the effects of grazing intensity in other parts of the world, such as Israel (Kidron, 2014, 2016), Mongolia (Onda et al., 2007), USA (Neff et al., 2005; Warren et al., 1986), Australia (Bartley et al., 2010), and New Zealand (Donovan & Monaghan, 2021; Elliott & Carlson, 2004).…”
Section: Introductionmentioning
confidence: 99%